Design of LCL-Filter Based Three-level Active Power Filter - Nianchang Yu; Jiaqiang Yang; Shilan Chen; Ming Ye (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
This paper proposes an improved design of LCL-Filters for Three-Level Shunt Active power filters (APF). Available design principles are presented to achieve high compensation bandwidth and low switching frequency current. Then, affecitons of different parameters are taken into consideration of constraints on LCL-Filter design with detail analysis of ripple current. A simple and practical design procedure of LCL-Filter for Three-Level APF is subsequently proposed. The first step is to choose the resonant frequency of LCL-Filter according to the highest order harmonic needed to be compensated. Then it is aim to optimize the parameters of the LCL-Filter based on the design principles and constraints. The simulation results verify the effectiveness of the proposed method. DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.3441